The faith and modern thought: six lectures - Temple, William ((ATLA monograph preservation program ; ATLA fiche 1989-0704), 1913)
The grounds of our belief in God -- Revelation and faith -- The historic basis of Christianity -- The person of Christ -- The Atonement and the problem of evil -- The Spirit, the church and the life eternal.